CHARACTERIZATION AND THE RELEASE TEST OF ANTI-AGING TRETINOIN IN NANOEMULSION USING OLIVE OIL - Tristiana Erawati M.; Widji Soeratri (UNEJ e-Proceeding)
People are more and more desire a youthful andattractive appearance. Aging of the skin can be theresult of a normal process that involves a lowerrate of metabolic activities and is calledchronologic aging. Photoaging is the consequenceof chronic sun exposure and manifests clinicallywith fine and coarse wrinkling, roughness, dryness,laxity, shallowness, pigmentary mottling,telangiectasia, and in some cases withpreneoplastic and neoplastic changes (Stefanaki etal., 2005). Tretinoin is a compound that is able toshow an effect of prevention and treatment ofwrinkles due to photo aging, acne, andinflammation of the skin. It is all-trans retinol isoxidized through retinal to its most activemetabolite (Kligman et. al, 1986). The effectivity ofan active ingredient is determined among othersby the ability to reach the site of action. To reachthe site of action the active ingredients used orallyor topically must first dissolve, release thenabsorbed or penetrates through the membraneand then diffuses into the site of action. Tretinoinpractically insoluble to increase it usednanoemulsion delivery as a vehicle. Solubility isone of the factors of drug absorption. Highersolubility of drug caused higher amount of drug toabsorb. Smaller droplet of emulsion caused rapiddrug release. In this study tretinoin loaded innanoemulsion using olive oil than it characterizedand test of tretinoin release compared withtretinoin in emulsion. Olive oil used as oil phase innanoemulsion as known it widely used in cosmetic.MATERIAL AND METHODSResearch MaterialsTretinoin (PT. Cortico Mulia), olive oil , Tween 80(Sigma Aldrich), Span 80 (Sigma Aldrich), ethanol96 % (E-Merck), NaH2PO4 (E-Merck) and Na2HPO4(E-Merck), aquademineralisata (PT Brataco).Research InstrumentsStirrer plate (Dragon Lab MS-Pro), ultrasonic(Branson 3510), shaker machine (Wine shake), pHmeter (Eutech Instruments pH 700), particleanalyzer (Delsa Nano C), Franz diffusion cell withcellophane membranes, spectrophotometer(Shimadzu UV-1800), Transmission ElectronMicroscopy (TEM-type JOEL JEM-1400), lightmicroscope.